The Risk for Prostate Cancer With Calcium Channel Blockers: A Systematic Review, Meta-Analysis, and Meta-Regression. Issue 1 (January 2023) - Rotshild, Victoria; Rabkin, Natalie; Matok, Ilan
Background: For decades, conflicting results were published regarding the increased risk of Prostate cancer (PCa) among calcium channel blocker (CCB) users. Objective: We aimed to evaluate the association between PCa and CCB exposure and assess moderating factors. Methods: We performed a systematic literature search in PubMed, Embase, and Cochrane databases for observational and randomized studies published until November 2020 with no language limitations, including data on the risk for PCa in CCB users compared with non-CCB users. We applied a random-effects model meta-analysis to pool results. In addition, we investigated potential moderating factors, such as CCB type, study type, participants' age, and duration of exposure, using meta-regression methods. Results: In our primary analysis, we included 18 studies. A statistically significant 5% increase in the risk for PCa was observed among CCB users (risk ratio [RR] = 1.05; 95% confidence interval [CI]: 1.01-1.10), with no significant association between the duration of exposure to CCBs and the risk for PCa (RR = 1.08; 95% CI: 0.98-1.19 for exposure for < 5years and RR = 1.01; 95% CI: 0.9-1.14 for exposure ≥ 5 years). The association remained statistically significant for the subgroup of dihydropyridines (RR = 1.13; 95% CI: 1.05-1.22). In addition, the association was not influenced by participants' age. Conclusion and Relevance: CCBs are an important modality in treating hypertension. The 5% increased risk observed in the current meta-analysis could be influenced by residual confounding factors and should not affect hypertension treatment guidelines until more studies provide additional clinical information.